Yrast states and electromagnetic reduced transition properties of ¹²²Te by means of interacting Boson Model-1 - Shelley, A.; Hossain, I.; Sharrad, Fadhil I.; Abdullah, Hewa Y.; Saeed, M.A. (Вопросы атомной науки и техники, 2015)
In this paper, the yrast states and the electric reduced transition probabilities B(E2) ↓ from gamma transition 8⁺ to 6⁺, 6⁺ to 4⁺, 4⁺ to 2⁺ and 2⁺ to 0⁺ states of neutron rich ¹²²Te nucleus in the frame work of Interacting Boson Model-I (IBM-I) have carried out. The calculated results have been compared with the available experimental values. The ratio of the excitation energies of first 4⁺ and 2⁺ excited states (R₄/₂), have also been calculated for this nucleus. An acceptable degree of agreement between the predictions of IBM-I model and experiment is achieved. Moreover, as a measure to quantify evolution, we studied the transition rate R = B(E2 : L⁺ → (L - 2)⁺ ) / B(E2 : 2⁺ → 0⁺ ) of some of the low-lying quadrupole collective states in comparison to the available experimental data. The IBM-I formula for energy levels and the reduced transition probabilities B(E2) have been analytically deduced in the U(5) limit for a few yrast states transitions in ¹²²Te isotope. Отримані yrast-стани і приведені вірогідності електричних переходів B(E2) ↓ від γ-переходів між станами 8⁺ і 6⁺, 6⁺ і 4⁺, 4⁺ і 2⁺ а також 2⁺ і 0⁺ у багатому нейтронами ядрі ¹²²Te в рамках моделі взємодіючих бозонів (IBM-I). Наслідки розрахунків порівняні з наявними експериментальними величинами. Відношення енергій збудження (R₄/₂) перших збуджених станів 4⁺ і 2⁺ для данного ядра були також розраховані. Отримано задовільне узгодження між передбаченнями моделі IBM-I та експериментом. Крім цього, для оцінки процесу ми вивчили співвідношення переходів R = B(E2 : L⁺ → (L - 2)⁺) / B(E2 : 2⁺ → 0⁺) між кількома низьколежачими квадрупольними колективними станами в порівнянні з відомими експериментальними даними. IBM-I формула для енергетичних рівнів та приведені вірогідності переходів B(E2) була отримана аналітично в U(5)-наближенні для кількох переходів між yrast-станами в ізотопі ¹²²Te . Получены yrast-состояния и приведенные вероятности электрических переходов B(E2) ↓ от γ-переходов между состояниями 8⁺ и 6⁺, 6⁺ и 4⁺, 4⁺ и 2⁺ а также 2⁺ и 0⁺ в богатом нейтронами ядре ¹²²Te в рамках модели взаимодействующих бозонов (IBM-I). Результаты расчетов сравнены с наличными экспериментальными величинами. Отношение энергий возбуждения (R₄/₂) первых возбужденных состояний 4⁺ и 2⁺ для данного ядра были также рассчитаны. Получено удовлетворительное согласие между предсказаниями модели IBM-I и экспериментом. Кроме этого, для оценки процесса мы изучили соотношение переходов R = B(E2 : L⁺ → (L - 2)⁺) / B(E2 : 2⁺ → 0⁺) между некоторыми низко лежащими квадрупольными коллективными состояниями в сравнении с доступными экспериментальными данными. IBM-I формула для энергетических уровней и приведенных вероятностей переходов B(E2) была получена аналитически в U(5)-приближении для нескольких переходов между yrast-состояниями в изотопе ¹²²Te .